2020
DOI: 10.1111/bcpt.13480
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine and other antipsychotics combined with opioids in legal autopsy cases: A random finding or cause of fatal outcome?

Abstract: Opioid poisoning is a frequent cause of death in drug addicts and occurs with opioid treatment. Quetiapine is often found in forensic autopsies and may increase the risk of fatal opioid poisoning by enhancing sedation, respiratory depression, hypotension and QT prolongation. We systematically searched for studies of acute toxicity of quetiapine or other antipsychotics combined with morphine or methadone. Case reports describing toxicity of quetiapine combined with morphine or methadone were also included. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 85 publications
(205 reference statements)
3
20
0
Order By: Relevance
“…Quetiapine and opioids are both sedatives and can induce respiratory depression, creating a basis for pharmacodynamic interactions. 14 In the present study, quetiapine was found in an increasing proportion of fatal opioid poisonings over time. This is in line with other studies showing an increase in the number of calls concerning quetiapine to a poisoning centre and deaths related to quetiapine.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Quetiapine and opioids are both sedatives and can induce respiratory depression, creating a basis for pharmacodynamic interactions. 14 In the present study, quetiapine was found in an increasing proportion of fatal opioid poisonings over time. This is in line with other studies showing an increase in the number of calls concerning quetiapine to a poisoning centre and deaths related to quetiapine.…”
Section: Discussionsupporting
confidence: 51%
“…Data on the combined effects of opioids and quetiapine are sparse. Based on the literature, we previously suggested a possible additive effect of morphine and methadone with other antipsychotics such as acepromazine on sedation, respiratory depression and hypotension in animal studies 14 . Therefore, we hypothesized that concomitant exposure to quetiapine and methadone or morphine might have additive effects.…”
Section: Introductionmentioning
confidence: 97%
“…This may also reflect an altered prescription pattern. Quetiapine is one of the most used antipsychotics in Denmark, 15 and may, additionally, have abuse potential 16…”
Section: Discussionmentioning
confidence: 99%
“…Such high levels of comorbidity are potentially due to, inter alia, shared genetic and environmental factors increasing SUD vulnerability [for review see ( 4 , 5 )] or to alleviate cognitive and psychotic symptoms ( 6 ). Use of psychoactive substances can interfere with antipsychotic medication ( 7 ), are associated with reduced adherence to SCZ interventions ( 8 ), and can lead to symptom exacerbation ( 9 ). There are mixed findings with respect to antipsychotics for treating SUDs in SCZ and preliminary support for the use of naltrexone in reducing alcohol use in SCZ ( 10 ).…”
Section: Introductionmentioning
confidence: 99%